The Reform of Consumer Protection Law: Comparison of Indonesia, Vietnam, and Ghana - Kadir, M. Yakub Aiyub; Arifin, Miftah; Disantara, Fradhana Putra; Thuong, Mac Thi Hoai; Nutako, Briggs Samuel Mawunyo (Universitas Negeri Surabaya, 2024)
Consumer protection has become a major challenge in Indonesia, Vietnam, and Ghana, facing gaps in information, bargaining power, and access to legal justice, especially in the context of technological development and globalization. This research seeks to evaluate the comparison in the area of consumer protection law between Indonesia, Vietnam, and Ghana and what legal reforms can be adopted in the case of Indonesia from best practices in Vietnam and Ghana. The study is a normative legal research in which the conceptual and the regulatory approaches are utilized to assess the laws on consumers in Indonesia, Vietnam, Ghana, and by examining of different legal documents i.e. primary, secondary, and tertiary sources and after that employing descriptive qualitative analysis on the data. The results show that countries, including Indonesia, Vietnam, and Ghana vary widely across and between themselves regarding the nature of the laws, the supervision exercised, and even the enforcement of the laws. Indonesia is guided by the Consumer Protection Law (UUPK) with BPKN and BPSK as the overseeing bodies, while Vietnam is guided by the Law on Protection of Consumer Rights (LOPCR) which is enforced by the VCCA. Ghana which is at the moment developing a Consumer Protection Act is guided by the Food and Drugs Authority (FDA) in enforcing product supervision. All the three countries have a low consumer population even where the law is enforced and this has developed into a problem. In making practices and market interactions in Indonesia more transparent, it could apply solutions from Vietnam on information sharing and electronic dispute resolution and also consolidate the position of BPKN as it was done in Ghana in order to afford more efficient control over and defense of a digital market place against illicit activities